2019
DOI: 10.1177/2192568218825247
|View full text |Cite
|
Sign up to set email alerts
|

Safety Culture and Attitudes Among Spine Professionals: Results of an International Survey

Abstract: Study Design: International survey. Objective: A positive safety culture has been linked to better surgical outcomes, less hospital costs and less patient harm and severity-adjusted mortality, making safety attitudes relevant for society and both patient and health care provider. The aim of the current study is to assess attitudes toward safety culture among spinal care professionals. Methods: An online survey was distributed to members of AOSpine International in 2016. The survey consisted out of 3 parts: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 22 publications
2
6
1
17
Order By: Relevance
“…In the SAQ instrument, some studies show that “teamwork climate” reached the score for positive safety culture ( 12 , 18 , 27 ) , but in this study, the domain did not reach the median of 75 points, only approached. These results reflect a positive perception, since a good relationship between the team can have an influence on organizational climate, productivity, communication, care and health of workers ( 12 , 24 ) .…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In the SAQ instrument, some studies show that “teamwork climate” reached the score for positive safety culture ( 12 , 18 , 27 ) , but in this study, the domain did not reach the median of 75 points, only approached. These results reflect a positive perception, since a good relationship between the team can have an influence on organizational climate, productivity, communication, care and health of workers ( 12 , 24 ) .…”
Section: Discussioncontrasting
confidence: 79%
“…Among the participants in this study, there was a predominance of nursing technicians/assistants, corroborating several studies ( 11 , 13 , 15 - 17 , 21 , 24 - 25 ) whose samples were composed mostly of nursing team professionals. Only in a multinational study with health professionals from 68 countries ( 18 ) , physicians prevailed in the sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest perception of patient safety among the surgeons implies that they were the least optimistic of the existing safety culture. An international survey on safety culture and attitudes among spine professionals had earlier revealed that most of the respondents believe that the surgeon has responsibility for both the prevention of adverse events and improvement of the safety culture in the operating room [ 25 ]. Such a mindset could influence a more critical appraisal of patient safety among the surgeons compared to the perioperative nurses and the nurse anaesthetists.…”
Section: Discussionmentioning
confidence: 99%
“…Very few publications have evaluated the patient safety culture in the operating room, among them a Tunisian multicenter study [12], a Norwegian single-institution survey [22] and an American single-institution survey [23]. A few others utilized survey tools other than the HSOPS [24][25][26] but comparisons with these are not tenable owing to differences in the factor components.…”
Section: Discussionmentioning
confidence: 99%